Uji Aktivitas Tabir Surya Ekstrak Metanol Kulit Batang Kersen (Muntingia calabura L.) Secara In Vitro - Risna; Angga; Tika Ristiani (Proceeding of Mulawarman Pharmaceuticals Conferences, 2019)
ABSTRACT Kersen (Muntingia calabura L.) is a plant that is usually useful as a shade tree on the side of the road, which is thought to have the potential with sunscreen activity. This study aim to determine sunscreen activity of the bark based on %Te, %Tp and SPF values ??in vitro. The extraction was done by maceration using methanol solvent, and then phytochemical screening by color reaction test that showed the presence of flavonoids, phenolics, tannins, saponins, and terpenoid. Sunscreen activity and SPF values ??were determined by measuring the absorbance of extracts with several variations of concentration, using spectrophotometer. The results showed the best concentration for the sunscreen category was 700 ppm. Based on the value of %Te and %Tp, including standard suntan and sunblock categories. While based on the SPF value >15 shows that methanol extract is included in the category of ultra protection.